Crames - creative thinking activities to get your brain working. - Mowat, Ashley Mccabe (Brilliant Publications, 2012)
CRAMES are practical, easy-to-use creative games that get children thinking creatively. The stimulating trigger questions develop problem solving and creative thinking skills in activities that take as little as five minutes a day. No preparation is needed, just the willingness to think creatively. Trigger questions range from 'What if the sea turned everything it touched red?' and 'How many things can you think of that squeak?' to 'How is a museum like a story?' and 'Would you rather be a p ...